Penerapan Model Com-B untuk Memprediksi Minat Adopsi Pupuk Organik pada Petani Hortikultura di Kabupaten Bone Bolango - Rusni Olabu; Zulham Sirajuddin; Karlena Arsyad (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the factors influencing the adoption of organic fertilizers among horticultural farmers in Bone Bolango Regency using the COM-B framework (Capability, Opportunity, Motivation–Behavior). A quantitative approach was employed through a structured questionnaire survey administered to 68 respondents, determined using the Slovin formula and selected through accidental sampling. Data were analyzed using multiple linear regression to examine the effects of capability, opportunity, and motivation on organic fertilizer adoption behavior. The results indicate that motivation has a significant effect on adoption behavior, while capability and opportunity do not show significant effects. These findings suggest that internal drive, perceived benefits, and the intention to adopt are the primary determinants of adoption, whereas technical capacity and environmental support have not sufficiently differentiated adoption levels among farmers. In practice, several constraints remain, including limited technical skills, uncertainty in the availability of raw materials, and restricted access to facilities, information, and extension services. Therefore, strengthening technical training, implementing practice-based extension programs, providing demonstration plots, and fostering partnerships alongside policy support are essential to enhance the sustainable adoption of organic fertilizers.